« Contextualising French in the South African plurality : A sociolinguistic and didactic approach » - (:unkn) unknown (My University, 2010)
The democratic evolution occurring in South Africa, a country in which there are now eleven official languages, brought us to examine the position of French and to put it into perspective. Initially, our research seemed to indicate that its position was quite weak, leading us to question the relevance of French in the new South African configuration (Chapter 1), beyond its mere status as a « minority » Francophony The research is anchored in Sociolinguistics and Didactics and was built on a critique qualitative empirico-inductive approach, based on working with the stakeholders within the secondary and higher education structures of teaching and learning, through participative observations and comprehensive interviews. These observables are cross-referenced with studies undertaken on texts dealing with educational, linguistic and university reform as well as on political and media discourse on the subject of languages and identity (Chapter 2). Although the way in which the issue of otherness is dealt with in South Africa could have seemed « radical » coming form a partially external point of view, the notion of identity/otherness very quickly became fundamental in interpreting the observables (Chapter 3). It subsequently became clear that it was necessary to contextualise the South African plurality by drawing on cross-references from a variety of scientific fields in order to explicitly reveal ways in which French can be integrated into the challenges and projects facing South Africa. In this environment, there is a certain « laisser faire » which favours English and which presents plurilingualism as merely recognising multilingualism, thus revealing a paradoxical position with regard to that language. Indeed, the diversity of modes in which English is appropriated as an element of identity constitutes a socio-linguistic marker of a type of social democratisation. By the same token, English can also be considered as concealing the real issues ar
Keywords: African Research